PENAFSIRAN FEMINIS: EKSPLORASI FEMINISME DALAM TAFSIR AL-QUR’AN - Hasan Ahmad Hasan, Devy Meris Lazimatun Nazhifah (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2024)
Feminist exegesis is a genre of its own that emerged in the contemporary era when gender issues became global issues. This interpretation paradigm begins with the assumption that the basic principles of the Qur'an in the relationship between men and women are justice (al-'adalah), equality (al-musawah), propriety (al-ma'ruf), deliberation (shura). If there are classical interpretation products that contradict these principles, they will be considered inappropriate, especially when applied in the current context, because the situation and conditions are clearly different between the past and present. The analysis model used in the feminist interpretation paradigm is gender analysis, which clearly distinguishes between nature as something that cannot change, and gender as a social construct that can change. It is natural that the hermeneutic approach with the thematic interpretation method finally becomes the choice in studying verses about gender relations. Because with such a methodology, it is hoped that the interpretation products will be more intersubjective and critical in seeing the problem of gender relations.